Correlation between cell wall buckling and deformation banding in a closed-cell foam. (September 2019) - Chai, H.W.; Li, H.Y.; Xiao, X.H.; Huang, J.Y.; Luo, S.N.
Abstract: We investigate deformation dynamics in a widely used closed-cell foam of polymethacrylimide under uniaxial compression with in situ X-ray computed tomography and digital volume correlation. Axial strain mapping demonstrates discrete deformation bands nucleated in sequence across the sample. A buckling strength index is proposed to quantify the buckling resistance of cell walls, based on their morphology extracted via an edge-segmentation procedure developed in this work. The spatial distribution of the weakest cell walls is correlated well with the location and nucleation sequence of deformation bands, and can be used for predicting deformation banding. Graphical Abstract: Unlabelled Image